Penerapan Activity-Based Costing (ABC) dalam Menentukan Harga Pokok Produksi pada UMKM Ngucekin Laundry "Mencuci Dengan Hati" - Agus Wahyudi; Kristina Jijin Bhau; Maria Melania Deflina Djawa; Cahyani Rika Prawesty; Maria Cindi Elvira Manek (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to apply the Activity-Based Costing (ABC) method in calculating the cost of goods manufactured (COGM) at Ngucekin Laundry, a service-based business offering dry cleaning, ironing, curtain washing, and bed cover cleaning. The ABC method is utilized to gain more accurate cost information by allocating costs based on activities and relevant cost drivers. This approach is essential for improving pricing effectiveness and business strategy, particularly for MSMEs facing complex service production processes. The findings reveal significant differences between the production costs calculated using the ABC method and the currently applied pricing, with some services showing margins exceeding 60%. These results indicate the need to reassess the current pricing structure to better reflect actual costs while remaining competitive in the market. Overall, the implementation of the ABC method proves to provide a clearer cost perspective and supports more precise managerial decision-making..